Amiodarone and ventricular fibrillation amplitude of spectral area in patients with out-of-hospital cardiac arrest. Is there an effect?. (3rd October 2022) - Gentile, F R; Compagnoni, S; Baldi, E; Primi, R; Bendotti, S; Currao, A; Aramendi, E; Isasi, I; Contri, E; Palo, A; Savastano, S
Abstract: Background: The use of antiarrhythmic drug therapy is usually recommended in addition to defibrillation in shockable cardiac arrest. The role of the amplitude spectral area (AMSA) of ventricular fibrillation as a predictor of defibrillation efficacy has been established, but little is known about how amiodarone could affect AMSA values. Purpose: The aim of our study was to evaluate whether the administration of amiodarone during resuscitation could affect AMSA and to verify if AMSA preserves its predictive role of shock success in OHCA patients treated with amiodarone. Material: All the OHCAs with an attempted resuscitation and at least one shockable rhythm which occurred from January 2015 to December 2020 in the province of Pavia were considered. AMSA values were calculated by retrospectively analyzing the data collected by the Corpuls 3 monitors/defibrillators (Corpuls, Kaufering, Germany) used in the field and by considering a pre-shock interval of 2 seconds. Results: Of 4619 OHCAs, 697 underwent attempted CPR with at least one shock delivered. Of these, AMSA was available on 250 patients (male 84%, median age 67 years), for a total of 830 shocks, of which 534 (64%) shocks were in patients receiving amiodarone. The success rate of each single shock was similar in the two groups (amiodarone 42% vs no amiodarone 41%, p=0.68). The AMSA median values were significantly lower in the amiodarone group as compared to the non-amiodarone group when shocks were delivered to patients older than 67 years old [median difference: 1.55 mV Hz (95% CI 0.6–2.5), p=0.0013] or receiving bystander CPR [median difference 0.9 mV Hz (95% CI 0.1–1.8), p=0.03] or after more than 33 minutes from the emergency call to each single shock [median difference: 0.91 mV Hz (95% CI 1.9–0.01), p=0.047]. AMSA value lower than the median (8.3 Hz mV) was associated with a lower probability of shock success (19% vs 64%, p<0.001). According to a multivariate analysis corrected for age, sex, witnessed status, call to shock time and bystander CPR, the probability of having AMSA lower than the median was independently associated with the administration of amiodarone [OR 1.5 (95% CI 1.1–2.1) p=0.009]. At ROC curves analysis, amongst patients receiving amiodarone, AMSA was confirmed to be a predictor of both shock success and ROSC [AUC 0.755 (95% CI 0.72–0.79), p<0.001 and AUC 0.826 (95% CI 0.79–0.86), p<0.001 respectively], similarly to the general population [AUC 0.778 (95% CI0.75–0.81), p<0.001; AUC 0.817 (95% CI 0.79–0.84), p<0.001]. Conclusions: Amiodarone administration is independently associated with lower values of AMSA. This could justify the lack of benefit from amiodarone administration in term of defibrillation success which would be expected by the administration of an antiarrhythmic drug during the resuscitation. Moreover, AMSA maintains its predictive value for shock success and ROSC rate in patients receiving amiodarone as well as in the general population. Funding Acknowledgement: Type of funding sources: None.